Promoting STEM-Creative Skills in High School Students: Renewable Energy in Island Regions - Jamaludin; Batlolona, John Rafafy; Barus, Carolina Sri Athena (Pascasarjana Universitas Mataram, 2025)
This community service activity aims to increase students' understanding of renewable energy through a STEM education approach at SMA Negeri 57 Maluku Tengah. In this activity, students are invited to design and build a simple windmill model, which not only introduces basic physics concepts but also encourages their creativity and critical thinking skills. The main results of this activity show that students experienced an increase in knowledge and practical skills related to renewable energy. In addition, they also showed an increased interest in science and technology, as well as the ability to collaborate in groups. The main conclusion of this activity is that a project-based approach in STEM education is effective in developing 21st-century skills in students, as well as the importance of integrating the concept of renewable energy into the curriculum to prepare the younger generation to face environmental challenges in the future. This activity also emphasizes the need for teacher training to support the implementation of better STEM education. Thus, strengthening STEM education that focuses on renewable energy can be a strategic step in preparing students to face increasingly complex environmental challenges.